An advanced absorbing boundary for wave propagation analysis in saturated porous media. Issue 136 (September 2020) - Hu, Dan; Li, Fen; Zhang, Lei; Zhang, Kaiyin
Abstract: In establishing the numerical model to simulate the saturated soil-structure interaction subjected to dynamic loadings, the absorbing boundary conditions are usually applied to simulate the wave propagation in the field. In this study, a type of viscous boundary in conjunction with the domain reduction method (DRM) is proposed as an advanced absorbing boundary. The performance of this advanced absorbing boundary is examined by comparing the seismic responses of rectangular tunnel modeled with different boundary conditions in FLAC3D. The numerical results suggest that the advanced absorbing boundary has advantages over the other types of boundaries in minimizing the wave reflection at the numerical boundaries. Furthermore, the proposed advanced absorbing boundary is also employed for the seismic investigation of clay-pile systems, the results of which compare favorably well with the corresponding seismic centrifuge test results. The numerical analysis results indicate that the advanced absorbing boundary proposed in this study can be effectively employed for the efficient dynamic analysis of structures founded on the saturated porous media. Highlights: An effective absorbing boundary is proposed for the efficient dynamic numerical analysis of two-phase media. Favorable performance of this new absorbing boundary is confirmed in comparison with conventional absorbing boundaries. Validity of this new absorbing boundary is favorably examined by seismic centrifuge test results on clay-pile systems.